Visible Cohesion: A Comparison of Reference Tracking in Sign, Speech, and Co‐Speech Gesture. (4th December 2014) - Perniss, Pamela; Özyürek, Asli
Abstract Establishing and maintaining reference is a crucial part of discourse. In spoken languages, differential linguistic devices mark referents occurring in different referential contexts, that is, introduction, maintenance, and re‐introduction contexts. Speakers using gestures as well as users of sign languages have also been shown to mark referents differentially depending on the referential context. This article investigates the modality‐specific contribution of the visual modality in marking referential context by providing a direct comparison between sign language (German Sign Language; DGS) and co‐speech gesture with speech (German) in elicited narratives. Across all forms of expression, we find that referents in subject position are referred to with more marking material in re‐introduction contexts compared to maintenance contexts. Furthermore, we find that spatial modification is used as a modality‐specific strategy in both DGS and German co‐speech gesture, and that the configuration of referent locations in sign space and gesture space corresponds in an iconic and consistent way to the locations of referents in the narrated event. However, we find that spatial modification is used in different ways for marking re‐introduction and maintenance contexts in DGS and German co‐speech gesture. The findings are discussed in relation to the unique contribution of the visual modality to reference tracking in discourse when it is used in a unimodal system with full linguistic structure (i.e., as in sign) versus in a bimodal system that is a composite of speech and gesture.